PENGARUH PENGUASAAN TATA BAHASA TERHADAP KEMAMPUAN MENYIMAK BAHASA INGGRIS - Unpris Yastanti (LPPM Universitas Bina Sarana Informatika, 2015)
The objective of this research is to know the effects of grammar mastery towards student’s listening skill. The research methodology that is used Eksperimen methodology. The subject of this research is taken from the whole population students of at Private Universities in Jakarta by the range of Academy Foreign Language Bina Sarana Informatika and sampel is taken from fourth term. This research has been done from April until August 2014. From this research shown that the result of SPSS Fo=121,637 and sig=0,000(0,000<0,05), it can be concluded that the grammar mastery give significant effect towards student’s listening skill. Keywords: Grammar Mastery, Listening Skill, Teaching